2007
DOI: 10.4269/ajtmh.2007.76.129
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia on Children and Flies After Mass Antibiotic Treatment for Trachoma

Abstract: There are various approaches to control trachoma. These include the elimination of the ocular strains of Chlamydia trachomatis that cause the disease and to decrease the spread of infection by other measures such as fly control. Here, we examined how these two are related (i.e., how treating children with antibiotics affects carriage of Chlamydia by flies). Flies were collected in villages that had received mass oral azithromycin distribution and were compared with flies in untreated villages. Polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…A study in The Gambia found a similar association between ocular C. trachomatis infection and age of the child, 6 and 12 months after mass treatment with azithromycin, and also found evidence of increased risk due to lack of latrine access at 6 months and ocular secretions at 12 months post-treatment (Burton et al 2005). In our study, flies, nasal and ocular discharge were not significant risk factors for C. trachomatis infection after MDA, only age and mass antibiotic treatment may reduce the transmission role of flies (Lee et al 2007). Increased frequency of MDA was associated with further reductions in C. trachomatis infection.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A study in The Gambia found a similar association between ocular C. trachomatis infection and age of the child, 6 and 12 months after mass treatment with azithromycin, and also found evidence of increased risk due to lack of latrine access at 6 months and ocular secretions at 12 months post-treatment (Burton et al 2005). In our study, flies, nasal and ocular discharge were not significant risk factors for C. trachomatis infection after MDA, only age and mass antibiotic treatment may reduce the transmission role of flies (Lee et al 2007). Increased frequency of MDA was associated with further reductions in C. trachomatis infection.…”
Section: Discussionsupporting
confidence: 85%
“…2005). In our study, flies, nasal and ocular discharge were not significant risk factors for C. trachomatis infection after MDA, only age and mass antibiotic treatment may reduce the transmission role of flies (Lee et al. 2007).…”
Section: Discussionmentioning
confidence: 60%
“…Chlamydia trachomatis has been detected by polymerase chain reaction in around 20% of Musca sorbens caught on the faces of children in Ethiopia (Jones 1975; Miller et al. 2004a; Lee et al. 2007) and intervention trials to reduce fly density have been associated with a reduction in active trachoma in The Gambia (Emerson et al.…”
Section: Transmission Of Chlamydia Trachomatis Infectionmentioning
confidence: 99%
“…Adult M. sorbens feed on ocular and nasal secretions to obtain nutrition and liquid [2], and in doing so can transmit Chlamydia trachomatis, the bacterium that causes trachoma, from person to person. Chlamydia trachomatis DNA has been found on wild caught M. sorbens [3][4][5], and a laboratory study demonstrated mechanical transmission of Chlamydia psittaci between the eyes of guinea pigs by the closely related Musca domestica [6]. Strong evidence for the role of M. sorbens as a vector of trachoma comes from a cluster-randomised controlled trial that examined the impact of fly control interventions on trachoma prevalence [7].…”
Section: Introductionmentioning
confidence: 99%